THE INCREASE OF COMPETITIVENESS OF REGIONS’ ECONOMIC COMPLEX IN THE CONDITIONS OF DECENTRALIZATION - Наталія Юріївна Лега (Збірник наукових праць Черкаського державного технологічного університету: Серія: Економічні науки, 2019)
One of the important problems in the formation of local budgets is the provision of balanced socio-economic development of the regions and the formation of inter-budgetary relations, with the aim of increasing the level of financial self-sufficiency by increasing fiscal decentralization.